Sequential self-assembly and disassembly of curcumin hydrogel effectively alleviates inflammatory bowel disease. (3rd October 2022) - Zhang, Lele; Ren, Xingxing; Zhou, Peirong; Wu, Fangzheng; Liu, Li; Hai, Zijuan
Abstract : Sequential self-assembly and disassembly of curcumin hydrogel can effectively alleviate inflammatory bowel disease. Abstract : Inflammatory bowel disease (IBD) is a chronic and relapsing inflammatory disorder of the gastrointestinal tract with unclear etiology and insufficient therapeutic efficacy. The development of specific, effective and safe IBD treatment drugs is of great clinical significance. Curcumin (Cur) is a good candidate to prevent and manage inflammatory diseases (such as IBD) due to its antioxidant and anti-inflammatory effects with safety profile. However, its poor aqueous solubility and instability under physiological conditions greatly limit its therapeutic efficacy. Herein, we exploited a Cur precursor Cur-FFEYp to locally deliver and slowly release Cur at inflamed regions for treatment of IBD by a sequential self-assembly and disassembly strategy. The much higher catalytic efficiency of alkaline phosphatase (ALP) than esterase towards Cur-FFEYp validated the sequential ALP-induced self-assembly with the formation of Cur hydrogel and esterase-guided disassembly with the slow release of Cur. In cell and animal experiments, Cur-FFEYp can effectively enhance the anti-inflammatory effect of Cur on inflammatory macrophages and significantly alleviate two types of IBD. We envision that by using other biomarkers to conduct the sequential self-assembly and disassembly processes and replacing other drugs, our smart strategy could be easily adjusted for the treatment of more diseases or cancers.